Evaluation of Anti-Mullerian Hormone level as a marker of Ovarian Reserve and correlate it with Laparoscopic Surgery of Pelvic Endometriosis in Subfertile Patients - Abbasi, Sharmin; Siddiqua, Sehereen Farhad; Alam, Mohammad Noor A; Jesmin, Suha (BIRDEM Medical Journal, 2017)
Background: Endometriosis refers to the presence of endometrial glands and stroma outside the uterine cavity. About 10% causes of infertility are due to endometriosis. In women Anti-Mullerian hormone (AMH) level represents the ovarian follicular pool and has been suggested as the most reliable and reproducible marker to asses ovarian reserve. The gold standard approach of management of endometriosis with subfertility is laparoscopy. The objectives of this stydy are evaluation of AMH levels as a marker of ovarian reserve in subfertile patients with different stages of pelvic endometriosis, and correlate it with laparoscopic surgery. Methods: This was a cross sectional observational study on 59 subfertile patients from January 2014 to January 2017 in Anwer Khan Modern Medical College Hospital (AKMMCH). Main outcome measured on the basis of measurement of AMH levels in correlation with the age, types of subfertility, stages of endometriosis, unilateral or bilateral ovarian involvement, size of the cyst, number of the cyst and the impact of different procedures during laparoscopy on AMH levels. Results: Basal AMH levels significantly lower (p= 0.011 and p =0.001) before and after laparoscopy in primary subfertile patients than secondary subfertile patients and AMH significantly decreased (P<0.024) after laparoscopy in primary subfertile patients. AMH level significantly decreased (P<.001) after laparoscopic surgery of two ovaries. Mean serum AMH levels were decreased in moderate and severe stages of endometriosis after laparoscopy (3.01±.04 ng/ml and 2.15±.03ng/ml). Different surgical procedures of laparoscopy showed significant impact on serum AMH levels, in thermal cauterization (p=0.023) and excision plus cauterization (p=0.001) showed significant decreased of AMH. Conclusion: Serum AMH level decreased in many patients after laparoscopy to such an extent from where future fertility is possible. Birdem Med J 2018; 8(1): 30-34